2016
DOI: 10.1021/acs.jpcb.6b05119
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Heterogeneity in the Michaelis Complex of Lactate Dehydrogenase: An Analysis of Vibrational Spectroscopy Using Markov and Hidden Markov Models

Abstract: Lactate dehydrogenase (LDH) catalyzes the interconversion of pyruvate and lactate. Recent isotope-edited IR spectroscopy suggests that conformational heterogeneity exists within the Michaelis complex of LDH, and this heterogeneity affects the propensity toward the on-enzyme chemical step for each Michaelis substate. By combining molecular dynamics simulations with Markov and hidden Markov models, we obtained a detailed kinetic network of the substates of the Michaelis complex of LDH. The ensemble-average elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
2
20
1
Order By: Relevance
“…The LDH enzyme demonstrates instructive catalysis–dynamics relationships 6,8,10,2031 and plays an important role in metabolism. 36,4749 We optimized the expression and purification methods to produce human heart LDH at a high yield, which may be adapted to other LDH enzymes to facilitate research with this enzyme family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LDH enzyme demonstrates instructive catalysis–dynamics relationships 6,8,10,2031 and plays an important role in metabolism. 36,4749 We optimized the expression and purification methods to produce human heart LDH at a high yield, which may be adapted to other LDH enzymes to facilitate research with this enzyme family.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,10,2031 LDH catalyzes the final step of anaerobic glycolysis, the reduction of pyruvate to L-lactate using reduced nicotinamide adenine dinucleotide (NADH) as the hydride donor. This reaction is reversible with an equilibrium strongly favoring the reduction of pyruvate to l -lactate.…”
Section: Introductionmentioning
confidence: 99%
“…These developments required computational definition of the transition state parameters. , Slower protein motions that lead to catalytically productive complexes were also characterized (in a range of promoting vibrations). , Further refinements of this work using Markov state models have strengthened this approach. , Other important developments support the promoting vibration concept. First, we showed that in lactate dehydrogenase, the promoting vibration is a preferred thermal channel; i.e., the enzyme takes thermal energy and transmits it along this channel .…”
Section: Application Of Transition Path Sampling To Enzymatic Mechanismsmentioning
confidence: 92%
“…In contrast, data from our laboratory accrued over the past few years have supported the view that most vibrational frequency variation (in carbonyls, at least) can be explained through a static electric field–difference dipole effect (53, 91), not by bond weakening or strain (i.e., changes in the force constant) (103, 104). This represents a departure from how vibrational measurements (both infrared and Raman) have traditionally been interpreted in enzymology (105107), and efforts are ongoing to reinterpret this corpus of biochemical data within this physical framework (108, 109). …”
Section: Stark Spectroscopy and Electric Field Measurementsmentioning
confidence: 98%